17. FACTORS RELATED TO THE CARING DEMANDS OF PATIENTS AFTER SURGERY AT SURGERY DEPARTMENT OF MEDICAL CENTER GIA RAI, BAC LIEU CITY IN 2020 (Vietnam Journal of Community Medicine, 2022)
Objectives: Determine patients’ care needs and psychology after surgery and find some factors relatedto the caring needs of postoperative patients at Gia Rai Medical Center, Bac Lieu city, in 2020.Subjects and research methods: A cross-sectional descriptive study was conducted in the medicalcenter Gia Rai, Bac Lieu, in 2020. The toolkit was based on “Guidelines for nursing care for patientsaccording to Circular 07/2011/TT of the Ministry of Health” and related research.Results and discussions: All patients needed postoperative care (100%). Patients worried aftersurgery accounted for 89.9%, and up to 79.8% feared pain when injecting drugs. The results ofmultivariable logistic regression analysis showed that have a relationship between the needs of socialcare and gender (OR= 2,3, p < 0,005) and ethnicity (p 0,05).Conclusions and recommendations: Patients were high anxiety and needed care post-operative.Therefore, the patient needs to be explained and educated more after post-operative. In addition,the female and Kinh patients should pay attention because their needs caring were higher than othergroups.
Keywords: Needs for care, post-operative care, post-operative psychology, factors related to postsurgery.